Effect of Pepper Variety on the Susceptibility of Pepper Weevil Parasitoids. Issue 6 (12th December 2022) - Murillo-Hernández, Juan Eduardo; Lomeli-Flores, J Refugio; Rodríguez-Leyva, Esteban; Soto-Rojas, Lauro; Torres-Ruiz, Alfonso; Santillán-Galicia, Ma Teresa; Muñíz-Reyes, Érica
Abstract: Anthonomus eugenii Cano (Coleoptera: Curculionidae) is a key pest of cultivated peppers ( Capsicum species) in tropical and subtropical America. Here we evaluated the effect of five pepper varieties on the susceptibility of A. eugenii to the parasitoids Bracon sp. (Hymenoptera: Braconidae), Eupelmus cushmani (Crawford) (Hymenoptera: Eupelmidae), and Jaliscoa hunteri Crawford (Hymenoptera: Pteromalidae). Potential parasitism was estimated by comparative analysis of parasitoid ovipositor size and the depth to which host larvae develop inside the fruit. Highest potential parasitism rates were achieved by Bracon sp. and E. cushmani on árbol and habanero peppers (84–99%) while the lowest rates were achieved by J. hunteri on serrano, bell, and jalapeño (7–18%). To validate potential parasitism rates, the actual parasitism rate by Bracon sp. and J. hunteri on three varieties of peppers was assessed. Actual parasitism rates of A. eugenii larvae in árbol were similar for Bracon sp. and J. hunteri (33%), while on bell and jalapeño Bracon sp. achieved 24% and 13% parasitism and J. hunteri achieved 14% and 8%, respectively. In most cases, actual parasitism was lower than estimated potential parasitism, although the latter had a notable predictive power (predicted R 2 = 0.84). Results showed that the host was more vulnerable on small-fruited varieties because larvae were closer to the pericarp and could be reached by parasitoid ovipositors; likewise, in varieties with little placenta and seed, some larvae fed in the pericarp, where they were more vulnerable.